Analyzing Factors Influencing In-Game Purchase Intention of Virtual Items: Case Study of PlayerUnknown’s Battleground Mobile (PUBG-M) - Briliana, Regita; Qastharin, Annisa Rahmani (Journal of Business and Management, 2021)
PlayerUnknown’s Battleground Mobile (PUBG-M) is the highest-earning battle royale game in the world. Their revenue mostly come from China and United States. Indonesia are a potential market for PUBG-M. This study aims to know factors influencing Indonesian users’ PUBG-M in-game purchase intention and examine loyalty towards the game relationships to factors that could influence in-game purchase intention. A quantitative survey were conducted among 338 respondents who have purchased PUBG-M virtual items and using Partial-Least Square (PLS) - Structural Equation Modeling (SEM) to analyze relationships between variables and purchase intention. The result indicates that game satisfaction, loyalty towards the game, social relationships and self-image, good price, character competencies and playfulness significantly influences in- game purchase intention. This study also finds that loyalty towards the game mediates factors influence in-game purchase intention. Game developers should enhance users’ satisfaction and loyalty, as well as playfulness and character competencies, while also increasing user’s social value and lowering the in-game purchase price. This findings could assist PUBG-M game developers a better approach in determining which marketing strategy to implement in order to increase game profitability and seize opportunities in Indonesia by considering Indonesian users’ purchase intention.Keywords: Purchase Intention; In-Game Purchase; Virtual Items; Indonesia; PUBG-M; Loyalty towards the Game.